REER Imbalances and Macroeconomic Adjustments in the Proposed West African Monetary Union - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2013)
With the spectre of the Euro crisis hunting embryonic monetary unions, we use a dynamic model of a small open economy to analyze REERs imbalances and examine whether the movements in the aggregate real exchange rates are consistent with the underlying macroeconomic fundamentals in the proposed West African Monetary Union (WAMU). Using both country-oriented and WAMU panel-based specifications, we show that the long-run behavior of the REERs can be explained by fluctuations in the terms of trade, productivity, investment, debt and openness. While there is still significant evidence of cross-country differences in the relationship between underlying macroeconomic fundamentals and corresponding REERs, the embryonic WAMU has a stable error correction mechanism with four of the five cointegration relations having signs that are consistent with the predictions from economic theory. Policy implications are discussed and the conclusions of the analysis are a valuable contribution to the scholarly and policy debate over whether the creation of a sustainable monetary union should precede convergence in macroeconomic fundamentals that determine REER adjustments.
Keywords: F31; F33; F42; F61; O55; 330; Exchange rate; Macroeconomic impact; Proposed WAMU